Mechanisms Involved in the Selective Transfer of Long Chain Polyunsaturated Fatty Acids to the Fetus - Gil-Sánchez, Alfonso; Demmelmair, Hans; Parrilla, JJ; Koletzko, Berthold; Larqué, Elvira (Frontiers in Genetics, 2011)
The concentration of long chain polyunsaturated fatty acid (LCPUFA) in the fetal brain increases dramatically from the third trimester until 18 months of life. Several studies have shown an association between the percentage of maternal plasma docosahexaenoic acid (DHA) during gestation and development of the cognitive functions in the neonate. Since only very low levels of LCPUFA are synthesized in the fetus and placenta, their primary source for the fetus is that of maternal origin. Both in vitro and human in vivo studies using labelled fatty acids have shown the preferential transfer of LCPUFA from the placenta to the fetus compared with other fatty acids, although the mechanisms involved are still uncertain. The placenta takes up circulating maternal non-esterified fatty acids (NEFA) and fatty acids released mainly by maternal lipoprotein lipase and endothelial lipase. These NEFA may enter the cell by passive diffusion or by means of membrane carrier proteins. Once in the cytosol, NEFA bind to cytosolic fatty acid-binding proteins for transfer to the fetal circulation or can be oxidized within the trophoblasts and even re-esterified and stored in lipid droplets (LD). Although trophoblast cells are not specialized in lipid storage, LCPUFA may up-regulate peroxisome proliferator activated receptor-γ (PPARγ) and hence the gene expression of fatty acid transport carriers, fatty acid acyl-CoA synthetases and adipophilin or other enzymes related with lipolysis, modifying their rate of placental transfer and metabolization. The placental transfer of LCPUFA during pregnancy seems to be a key factor in the neurological development of the fetus. Increased knowledge on the factors that modify placental transfer of fatty acids would contribute to our understanding of this complex process.